O setor florestal como uma alternativa ao desenvolvimento socioeconomico na região da serra do sudeste do Rio Grande do Sul, Brasil - Souza, Sara Chagas de (2023)
The study aims to analyze the potential for new forest enterprises in seven towns in the Serra do Sudeste Region, Rio Grande do Sul, Brazil, with a focus on developing silviculture as a way to drive regional development. In order to understand the region's socio-economic functioning, information on land use obtained through Mapbiomas has been used. In addition, data from the Rural Environmental Registry (CAR) were considered for analyzing the land structure of rural properties. In order to determine the concentration of areas with existing planted forests in the region, the Gini Index has been used, and it has taken into consideration data obtained from environmental licenses issued by the environmental agency. Finally, to estimate the amount of available area for new enterprises, the areas previously mapped with silviculture by the State Foundation for Environmental Protection Henrique Luis Roessler (FEPAM) have been considered. A total of 1,476,701 hectares have been analyzed across 13 different land use classes. The main land use classes included grassland formation with 507,493 hectares, forest formation with 346,313 hectares, silviculture with 209,744 hectares, and soybean cultivation with 198,487 hectares. Regarding land structure, 65% of properties are larger than four fiscal modules, depicting the region as having medium and large rural properties. Out of the 874 licenses analyzed, totaling 114,662 hectares, 82% are controlled by legal entities (46 entrepreneurs), and 76% of the licensed area in the region belongs to six companies. The Gini Index has demonstrated a range varying from strong to very strong concentration, with an average value of 0.885. Finally, it has been identified that there is an area of 79,440 hectares available for new silviculture plantations in the seven towns. Within the studied area, there are 14 Units of Planning and Management (UPN) with different occupancy limits, size, and distance between forest masses. This quantity reaffirms the complexity of state legislation for silviculture companies, making the activity less attractive to new investors and less competitive with other crops in the region. Therefore, to enable silviculture to fully develop, it is necessary to stimulate production in small, medium, and large rural properties, as well as involving different types of entrepreneurs, whether individuals or legal entities, through partnerships with public-private institutions. Moreover, encouraging the formulation of new public policies that incentivize forest plantations is essential.